Improving fluid consumption of older people in care homes: an exploration of the factors contributing to under-hydration. (2nd March 2020) - Wilson, Jennie; Tingle, Alison; Bak, Aggie; Greene, Carolynn; Tsiami, Amalia; Loveday, Heather
Abstract : Age-related changes put older people at risk of dehydration, and care home residents are particularly vulnerable. Researchers at the University of West London outline their study that identifies the possible barriers and facilitators to optimising hydration in nursing homes, offering guidance for service improvement initiatives